Genome-Wide Analysis of Dof Genes and Their Response to Abiotic Stress in Rose (Rosa chinensis) - Nan, Hong; Ludlow, Richard A.; Lu, Min; An, Huaming (Frontiers in Genetics, 2021)
Dof (DNA binding with one finger) proteins play important roles in plant development and defence regulatory networks. Here, we report a genome-wide analysis of rose Dof genes (RcDof), including phylogenetic inferences, gene structures, chromosomal locations, gene duplications and expression diversity. In this study, a total of 24 full-length RcDof genes were identified in Rosa chinensis, which were assigned to nine distinct subgroups. These RcDof genes were unevenly distributed on rose chromosomes. The genome-scale syntenic analysis showed that segmental duplication events might have played a major role in the evolution of the RcDof gene family. Analysis of cis-acting elements revealed putative functions of Dofs in rose during development as well as under numerous biotic and abiotic stresses. Moreover, the expression profiles derived from qRT-PCR experiments showed distinct expression patterns in various tissues and gene expression divergence existed among the duplicated RcDof genes, suggesting a fundamentally functional divergence of the duplicated Dof paralogs in rose. Gene expression of the RcDofs under drought and salt stresses were also investigated. This study offered novel insights into the evolution of the RcDofs and will help further functional characterization of candidate genes.